Crop production practices and input use pattern in rice (Oryza sativa L.) cultivation in sub-mountainous region of Punjab, India - Raminder Singh Ghuman; Navneet Kaur Dhaliwal (Annals of Agricultural Research, 2023)
Rice (Oryza sativa L.) has been highly input intensive crop of sub-mountainous region of Punjab (India). Farmer’s fields are highly diverse with respect to the adoption of contrasting crop production practices, which involve variable input use. We studied long-term (2012-21) changes in crop production practices and input use in rice production at farmer’s fields to understand the temporal variation related to management induced change in crop productivity. The survey data revealed that area under un-recommended paddy varieties decreased from 39% in 2012 to 6 % in 2021. Area under direct seeded rice (DSR) has increased marginally from 2012 to 2021. Butachlor was the major herbicide used over the years with 71-82% respondents using it for weed control. Majority of farmers (~60%) apply urea in a range of 91-130 kg/acre, while since 2018 farmers applying 71-90 kg urea are also increasing. Over the years there has been significant decline in the trend of farmers regarding phosphorous application in both rice and wheat crops. The percentage of farmers going for rice residue burning decreased from 68 % to 9 %.